The influence of cyclic preloadings on cyclic response of Zbraslav sand. Issue 166 (March 2023) - Duque, J.; Roháč, J.; Mašín, D.; Najser, J.; Opršal, J.
Abstract: This article presents a comprehensive experimental investigation on Zbraslav sand under monotonic and cyclic loading. Initially, the material response at large strains was investigated by means of undrained monotonic triaxial tests with different initial mean effective stresses and relative densities. A set of oedometric compression tests with multiple unloading–reloading cycles and different initial relative densities was as well included to evaluate the material compressibility. In addition, several undrained cyclic triaxial tests were performed and analyzed under a wide range of initial conditions. In the aforementioned tests, the undrained cyclic resistance was investigated considering different types of drained or undrained cyclic preloadings and reconsolidation stages. The experimental results suggested that drained cyclic preloadings remarkably modified the subsequent rate of pore water pressure accumulation and increased the number of cycles to reach the defined failure criterion without affecting the stress–strain response. On the other hand, undrained cyclic preloadings presented a threshold which separated positive and negative effects in the subsequent undrained cyclic resistance. A comparison of the undrained cyclic resistance variation depending on the number of drained or undrained cyclic preloadings was also included. Highlights: Undrained cyclic preloadings have a threshold that separate positive and negative influences in the liquefaction resistance. Drained cyclic preloadings improve the liquefaction resistance of sands. Drained and Undrained preloadings modify the accumulation rates of sands under undrained cyclic loading. Experimental database for the calibration and validation of constitutive models.